Advancements in SARS-CoV-2 detection: Navigating the molecular landscape and diagnostic technologies - Nuha Almulla; Raya Soltane; Ahlam Alasiri; Abdou Kamal Allayeh; Taha Alqadi; Fatma Alshehri; Ahlam Hamad Alrokban; Sameh S. Zaghlool; Abdallah Z. Zayan; Karam F. Abdalla; Ahmed M. Sayed (Heliyon, 2024)
According to information from the World Health Organization, the world has experienced about 430 million cases of COVID-19, a world-wide health crisis caused by the SARS-CoV-2 virus. This outbreak, originating from China in 2019, has led to nearly 6 million deaths worldwide. As the number of confirmed infections continues to rise, the need for cutting-edge techniques that can detect SARS-CoV-2 infections early and accurately has become more critical. To address this, the Federal Drug Administration (FDA) has issued emergency use authorizations (EUAs) for a wide range of diagnostic tools. These include tests based on detecting nucleic acids and antigen-antibody reactions. The quantitative real-time reverse transcription PCR (qRT-PCR) assay stands out as the gold standard for early virus detection. However, despite its accuracy, qRT-PCR has limitations, such as complex testing protocols and a risk of false negatives, which drive the continuous improvement in nucleic acid and serological testing approaches. The emergence of highly contagious variants of the coronavirus, such as Alpha (B.1.1.7), Delta (B.1.617.2), and Omicron (B.1.1.529), has increased the need for tests that can specifically identify these mutations. This article explores both nucleic acid-based and antigen-antibody serological assays, assessing the performance of recently approved FDA tests and those documented in scientific research, especially in identifying new coronavirus strains.